Reassessment of the conservation status of Crocidura fingui, a shrew endemic to Príncipe Island, Gulf of Guinea - João C.T. Alves; Yodiney dos Santos; Patrícia Guedes; Ricardo Rocha (Oryx, 2024)
The Fingui white-toothed shrew Crocidura fingui, categorized as Data Deficient on the IUCN Red List, is endemic to Príncipe Island, Central Africa. It is currently known from < 10 sites and its ecology and any threats are largely unknown. We review its distribution and ecology, and any potential threats, based on camera-trap data, field observations and previously published and unpublished sightings. Crocidura fingui appears to have an island-wide distribution and to use a range of ecosystems, from native forests to urban areas. It is largely nocturnal and exhibits considerable spatiotemporal overlap with introduced mammals such as the African civet Civettictis civetta, domestic cat Felis catus and rats Rattus spp. The species has an area of occupancy < 500 km2 and is known from fewer than five locations, and its population is inferred to be affected by several introduced mammals. We recommend that it is recategorized as Endangered on the IUCN Red List.